2018
DOI: 10.1093/gbe/evy035
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Epidermal Differentiation Genes of Crocodilians Suggests New Models for the Evolutionary Origin of Avian Feather Proteins

Abstract: The epidermis of amniotes forms a protective barrier against the environment and the differentiation program of keratinocytes, the main cell type in the epidermis, has undergone specific alterations in the course of adaptation of amniotes to a broad variety of environments and lifestyles. The epidermal differentiation complex (EDC) is a cluster of genes expressed at late stages of keratinocyte differentiation in both sauropsids and mammals. In the present study, we identified and analyzed the crocodilian equiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 48 publications
5
50
0
Order By: Relevance
“…In crocodilians 22 CBP genes have been detected in both the American alligator ( A. mississippiensis ) and the saltwater crocodile ( C. porosus ; Holthaus et al, ), which is similar to the 20 and 21 genes identified in a previous study (Greenwold & Sawyer, ). Remarkably no less than 42 CBP genes were found in the Chinese alligator (Figure ; Supporting Information Figure S1, As), suggesting some variation in the number of these structural proteins among crocodilians.…”
Section: Cbp Genes and Structures In Different Sauropsida Cladessupporting
confidence: 77%
See 4 more Smart Citations
“…In crocodilians 22 CBP genes have been detected in both the American alligator ( A. mississippiensis ) and the saltwater crocodile ( C. porosus ; Holthaus et al, ), which is similar to the 20 and 21 genes identified in a previous study (Greenwold & Sawyer, ). Remarkably no less than 42 CBP genes were found in the Chinese alligator (Figure ; Supporting Information Figure S1, As), suggesting some variation in the number of these structural proteins among crocodilians.…”
Section: Cbp Genes and Structures In Different Sauropsida Cladessupporting
confidence: 77%
“…The cladogram is based on Dalla Valle, Nardi, Gelmi, et al () and 2010a that report these main subdivisions. The source for the number of CBPs was for snakes Holthaus et al (); for anolis Dalla Valle, Nardi, Bonazza, et al (2010b); for the Japanese gecko Liu et al (); for birds Greenwold et al (); for crocodilians Holthaus et al () and this review; for turtles Li et al () [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: The Cbp Loci In Sauropsidamentioning
confidence: 98%
See 3 more Smart Citations